Implementasi Algoritma C.45 Dalam Memprediksi Kualitas Aset Kendaraan Kantor - Chatarina Putri Salsabila; Aditya Wijayanto (Journal of Information System Research (JOSH), 2023)
Badan Keuangan dan Aset Daerah (BKAD) of Banyumas Regency is an institution under a government position consisting of several sub-sectors, one of which is the Assets Sub-sector. The BKAD Regional Asset Sub-sector in Banyumas Regency has a type of Goods Inventory Card (KIB) that has not been managed properly, including KIB for office vehicles making it difficult to make a proposal for office vehicle maintenance. Maintenance of office vehicles is the initial stage of replacing vehicles according to employee needs so that employee performance can be maximized. Forecasts for office vehicle maintenance are presented to facilitate the implementation of duties in carrying out business trips. The methods used in data collection are survey methods, literature, and interviews. The data collection method used in this report uses a quantitative method with the C.45 algorithm. Predicting the quality of office vehicles can carry out several stages such as reviewing office vehicles, classifying the condition of office vehicles, after that a decision is made on which vehicles are suitable for use or not suitable for use. Analysis of predicting the quality of office vehicles using the C.45 algorithm with the rapidminer application can produce results in the form of a decision tree that is used by the asset sub-sector in order to make a decision. Based on the prediction results of office vehicle quality, it can be concluded that office vehicles will be suitable for use if the year of purchase or procurement is more than 2000 and office vehicles will not be suitable for use if the year of purchase or procurement is less than or equal to 2000. If you want to compare the results obtained it is advisable to use other tools or algorithms to make the next report.